R&D and industrial concentration in the Indonesian manufacturing industry - Maman Setiawan; Rina Indiastuti; Achmad K. Hidayat; Endang Rostiana (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
This research investigates the relation between research and development (R&D) expenditure and the industrial concentration in the Indonesian manufacturing industry. Pooled least square dummy variable is applied to estimate the relation between the two variables. This research uses firm-level data taken from the survey of the manufacturing industry sourced from the Indonesian Bureau of Central Statistics. This research makes contributions in calculating the percentage of R&D expenditure using the recent data and freshly estimating the relation between R&D and industrial concentration in the industry. This research finds that the percentage of R&D expenditure is relatively low in the industry. There is also a declining trend in the percentage of the R&D expenditure from the period 1994-1995 to 2017. The higher industrial concentration increases the percentage of R&D expenditure. This research also finds that R&D expenditure can be higher in the firms with market power.
Keywords: 650; Indonesian manufacturing industry; industrial concentration; price-cost margin; R&D expenditure